Rate of convergence for Szász-Bézier operators - Gupta, Vijay (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We estimate the rate of convergence for functions of bounded variation for the Bezier variant of the Szasz operators S_n, α(f, x). We study the rate of convergence of S_n, α(f, x) for the case 0 < α < 1.